An Ontological Approach of the Cognitive and Affective Product Experience - Tavares, David Ribeiro; Canciglieri Junior, Osiris; Guimarães, Lia Buarque de Macedo; Rudek, Marcelo (Frontiers in Neuroergonomics, 2021)
The cognitive and affective design aims to attract consumers with products and new products that provide innovative experiences with the intense functional and “cognitive” impact such as ease of use, in addition to “affective” impact as the pleasure of consuming. However, it is difficult to anticipate the consumer's preferences and intentionality, because what happens inside his mind, brain, or subjective experience (wishes, needs, and preferences) is not accessible. This study's objective was to propose an ontological and multidisciplinary approach to the cognitive and affective product experience through an explanation framework and a conceptual model. The model was tested, and the preliminary results indicate that the proposal contributes positively to the advance of the explanation, evaluation and translation of the product experience.